Parents' Social Support And Adjustment To Students' Learning Motivation In Junior High School Country 18 Central Maluku - Nur Marwah Ely (Da'wa Faculty of Islamic State University Salatiga, 2023)
The decrease in learning motivation was caused by students not being consistent in studying at home, besides that students paid less attention to the teacher's explanations because students did not understand the material presented by the teacher which was caused by inadequate internet network access, lazy doing assignments and delaying in submitting assignments.The purpose of this study was to test empirically the relationship between parental social support and adjustment to student learning motivation at SMP Negeri 18 Central Maluku, with a total of 170 students. This study uses population research. Data collection used a learning motivation scale, parental social support scale, and self-adjustment scale. The data analysis used in this study used multiple linear regression analysis with an assumption test. The results showed that there was a very significant relationship between parental social support and adjustment to student learning motivation with a significance value of 0.000 (p <0.05), the higher parental social support and self-adjustment was able to increase student learning motivation.